Samorząd jako wartość cywilizacyjna - Kasiński, Michał (Annales. Etyka w Życiu Gospodarczym, 2008)
The core of the local self-government stems from the Western (Latin) civilization values.European Nations have always fought for the qualities and perseverance of local self government.Currently it is considered an attribute of local democracy, although in the European tradition it has longbeen related to the pluralist values of social life organization. The communes; freedom, and theirindependence from the local government have been derived from natural law and seen as a condition fora healthy social system. Contemporarily, local self-government as a law and ability for localcommunities to manage a range of public matters independently, has been anew recognized as a socialsystem value in uniting Europe. Yet there have also revived certain historical threats to the local selfgovernmentarisen from central and local bureaucracy, particularism, and bribing local power elites.In such case, the fight for a local government that complies with Latin civilizational values acquiresa special meaning.